A dental stool with chest support reduces lower back muscle activation. Issue 3 (2nd July 2016) - Tran, Viet; Turner, Reid; MacFadden, Andrew; Cornish, Stephen M.; Esliger, Dale; Komiyama, Kunio; Chilibeck, Philip D.
Abstract : Activation of back musculature during work tasks leads to fatigue and potential injury. This is especially prevalent in dentists who perform much of their work from a seated position. We examined the use of an ergonomic dental stool with mid-sternum chest support for reducing lower back muscle activation. Electromyography of lower back extensors was assessed from 30 dental students for 20 s during three conditions in random order: (a) sitting upright at 90° of hip flexion on a standard stool, (b) leaning forward at 80° of hip flexion on a standard stool, and (c) leaning forward at 80° of hip flexion while sitting on an ergonomic stool. Muscular activity of the back extensors was reduced when using the ergonomic stool compared to the standard stool, by 33–50% ( p  < 0.01). This suggests a potential musculoskeletal benefit with use of a dental stool with mid-sternum chest support.